A Reparable Hierarchical Key Distribution Protocol for Internet Environments - Lin Xiaodong Xing Yusen Yang Yixian Yang FangChun (Tongxin xuebao)
The following results are achieved in this paper:（1） A new reparable hierarchical key distribution protocol （KDP） for internet environments is proposed, and this new KDP performs like Internet Domain Name Service; （2） A feasible compromised key replacing scheme is shown; （3） A KDP design principle is finished; （4） Finally, an important error in is found and corrected.